Tools for Gamification Analytics: A Survey - Heilbrunn, Benjamin; Herzig, Philipp; Schill, Alexander (Proceedings of the 2014 IEEE/ACM 7th International Conference on Utility and Cloud Computing, 2014)
Application and gamification data contains valuable information about users and their behavior. This data can be used to measure the success of gamification projects, to analyze user behavior, and to continuously improve gamification designs. Existing software solutions promise support for analyzing game- and gamification-related data. However, research shows that most gamification projects do not monitor and analyze this data in an automated way, even though gamification experts are aware of its potential. In this survey paper we identify relevant software solutions and assesses them with regards to their fulfillment of user requirements in the gamification analytics domain. The survey results can be used by practitioners to make tool decisions. Furthermore, we identify gaps of current solutions that should be addressed by future work in the field of gamification analytics.